PERAN ORANG TUA DALAM PERKEMBANGAN KARAKTER EMOSIONAL ANAK PADA REMAJA DI DESA SUMURGENUK KECAMATAN BABAT KABUPATEN LAMONGAN - Dwi Damayanti, Luthfi; Nikmah, Khoirotun (-, 2026)
The development of emotional character in adolescents is a crucial aspect in shaping a healthy and balanced personality. During adolescence, individuals undergo rapid changes, including significant shifts in cognitive, emotional, social, and physical aspects. One of the main factors influencing this process is the role of parents. Parents serve as primary models for behavior and emotional expression, and their influence is essential in fostering emotional maturity in adolescents. The objectives of this research are: (1) To understand the role of parents in nurturing emotional development in adolescents. (2) To examine the emotional character development of adolescents. This study employed a field research approach with a descriptive qualitative method. Data were collected through interviews, observations, and documentation. The data analysis techniques used include data reduction, data display, and conclusion drawing. The findings of this study indicate that: (1) Parents play a key role in guiding adolescents by providing positive examples, emotional support, and establishing mutually agreed-upon rules at home. This approach significantly aids in the emotional development of adolescents in Sumurgenuk Village. (2) The emotional development of adolescents can be observed through their ability to manage emotions, maintain good relationships with parents and others, and their growing desire to be heard and emotionally valued. This demonstrates that many adolescents are already capable of expressing their opinions on various issues they face.Therefore, the role of parents in supporting the healthy emotional development of adolescents is essential. It not only strengthens the parent-child relationship but also helps shape emotionally mature adolescents who feel respected and acknowledged in their emotional experiences.